Kinetics of bile acid metabolism in experimental blind loop syndrome. Issue 12 (December 1975) - Bender, S; Sauer, H; Hoffmann, D
Abstract : In an experimental model of the contaminated small bowel syndrome, Eriksson's washout technique was used to study bile salt metabolism. Bile salt secretion rate was increased from 204-7 +/- SD 36-5 mumol/100 g body weight/24 h to 329-9 +/- 146-6, pool size from 33-4 +/- 5-4 mumol/100 g BW to 42-5 +/- 7-2, and biliary flow from 6-6 +/- 1-72 ml/100 g BW/24 h to 8-4 +/- 2.1. Detailed analysis of the washout curves gave indirect evidence of a short-circuit jejunohepatic shunt in the model contaminated small bowel syndrome. Parameters of this shunt were calculated with 9-1 mumol/100 g BW for 'short-circuit' pool size and 13-8 for its circulation frequency.